Cyclic voltammetry, electrochemical impedance and ex situ X-ray diffraction studies of electrochemical insertion and deinsertion of lithium ion into nanostructured organic-inorganic poly(3,4-ethylenedioxythiophene) based hybrids - Murugan, A. Vadivel; Reddy, M. V.; Campet, Guy; Vijayamohanan, K. (Journal of Electroanalytical Chemistry, 2007)
In this work, we discuss the electrochemical insertion and deinsertion of lithium into poly(3,4-ethylenedioxythiophene) PEDOT-V(2)O(5) nanohybrids by using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and powder ex situ X-ray diffraction (XRD) studies with special emphasis on their application potential as cathode materials for rechargeable Lithium batteries. The interlayer spacing of crystalline V(2)O(5) expands from 0.43 to 1.41 nm by the intercalation of PEDOT nanoribbons prepared by a microwave irradiation method. Cyclic voltammetry studies of PEDOT-V(2)O(5) hybrid at a slow scan rate of 0.058 mVs(-1) between 2.0-4.3 V vs. Li/ Li(+), demonstrates that structural transitions Of V(2)O(5) are suppressed and more facile intercalation features appear in terms of well-defined reversible cathodic and anodic peaks when compared to that at higher scan rate. Electrochemical Impedance studies of PEDOT-V(2)O(5) hybrid as cathode at ambient temperature with lithium metal foil as both counter and reference electrodes in 1 M LiPF(6) in a mixture of ethylene and diethylcarbonate (50:50 by volume) between the range 2.0-4.3 V reveals the usefulness of these materials. The observed capacity fading during cycling in terms of surface passivation and structural transformations is also investigated by CV, EIS and XRD analysis. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ex situ XRD studies; high capacity lithium batteries; impedance studies; nanostructured hybrid materials